PRINSIP KEHATI-HATIAN BANK SEBAGAI LANDASAN OPERASIONAL PENYELENGGARAAN PERBANKAN DIGITAL DI INDONESIA - Syifa Radhiyya Prasetiawan, (2023)
In this digitalization era, digital banking system in Indonesia is growing which indicated by the presence of the newcomer digital banks. The challenge for digital bank is to have a healthy competition by providing new innovation that is according with this fully digital banking services trend. This research uses by doctrinal research method with statute approach and case approach. This research analyzes about the mandatory regulation of prudential banking principles and the reasons why digital bank have to implement prudential banking principles in its business activity. The regulation of prudential banking principles found in Article 2 Undangundang Nomor 10 Tahun 1998. Besides that, the newer regulation about digital banking found in Peraturan Otoritas Jasa Keuangan Nomor 12/POJK.03/2021 and Peraturan Otoritas Jasa Keuangan Nomor 12/POJK.03/2018. A case in 2021 that involved digital bank 'Jenius' is an example of digital banking problems which did not apply prudential banking principles well. Digital banks always have to aware of their prudential banking principles to all of their operational activity. Indonesia needs the renewal of Undang-undang Perbankan, considering that the banking law regulation is more than 20 years old and the digital banking services will be long term product of Indonesian banking, so that its existence should be listed in Undang-undang Perbankan.